Higher chance of survival in patients with out-of-hospital cardiac arrest attributed to poisoning. (June 2022) - Hüser, Christoph; Baumgärtel, Matthias; Ristau, Patrick; Wnent, Jan; Suárez, Victor; Hackl, Matthias Johannes; Gräsner, Jan-Thorsten; Seewald, Stephan
Abstract: Aim of the study: Description and comparison of cohort characteristics and outcome of adult patients with out-of-hospital cardiac arrest (OHCA) attributed to poisoning (P-OHCA) versus patients with OHCA attributed to other medical causes (NP-OHCA). Methods: We included all patients who received cardiopulmonary resuscitation after OHCA between January 2011 and December 2020 from German emergency medical services with good data quality in the German Resuscitation Registry. Exclusion criteria: patients < 18 years of age or OHCA attributed to trauma, drowning, intracranial bleeding or exsanguination. Results: Patients with P-OHCA (n = 574) were significantly younger compared to NP-OHCA (n = 40, 146) (median age of 43 (35–54) years vs. 73 (62–82) years; p < 0.001). Cardiac arrest in P-OHCA patients was significantly less often witnessed by bystanders (41.8 % vs. 66.2 %, p < 0.001). Asystole was the predominant initial rhythm in P-OHCA patients (73.5% vs. 53.7%, p < 0.001) while ventricular fibrillation (VF) and pulseless electrical activity (PEA) were less common (9.2% vs. 25.1% and 16.2 % vs. 20.5%, p < 0.001). P-OHCA had a higher chance of survival with good neurological outcome at hospital discharge (15.2 vs. 8.8 % p < 0.001) and poisoning was an independent protective prognostic factor in multivariate analysis (OR 2.47, 95%-CI [1.71–3.57]). P-OHCA patients with initial PEA survival with good neurological outcome was comparable to initial VF (34.3 % vs. 37.7%). Conclusion: Patients in the P-OHCA group had a significantly higher chance of survival with good neurological outcome and PEA as initial rhythm was as favourable as initial VF. Therefore, in P-OHCA patients resuscitation efforts should be extended.